Interruptions in nutritional therapy in children with chronic diseases during the acute phase of critical illness and their effect on the administered volume - Zamberlan, Patrícia; de Torres, Petrovane Morais; Caires De Oliveira Achili Ferreira, Juliana; Carvalho, Werther Brunow; Delgado, Artur (Frontiers in Nutrition, 2025)
IntroductionUndernutrition is a common concern among critically ill children and adolescents in the hospital setting. Inadequate delivery of nutrition therapy (NT) can significantly contribute to the prevalence of undernutrition in pediatric intensive care units (PICUs).ObjectiveTo assess the impact of interruptions on the volume of NT delivered to children with basal chronic conditions, as well as the calories and proteins provided, during the acute phase in the PICU.MethodsA cohort of critically ill pediatric patients with basal chronic conditions was analyzed to evaluate the administration of enteral or parenteral nutrition. The focus was on the volume of NT not effectively delivered and the underlying causes of incomplete NT.ResultsA total of 120 children were included, the majority of whom were undernourished (47.5%) by body mass index-for-age (BMI/A). A significant proportion of the prescribed enteral (EN) or parenteral nutrition (PN) was not administered during the first and third days of evaluation. The most prevalent reasons for interruptions were procedures delays and complications arising during treatment in the PICU.ConclusionInterruptions in NT delivery are frequent among critically ill children; the volume of NT not delivered was greater on the third day for both EN and PN after initiation; procedures delays and mild gastrointestinal complications were the main causes of incomplete NT administration.